Dispersion relation of Lamb waves in cross-ply composite laminates using multi-layered models. (15th May 2021) - Saito, Osamu; Yu, Fengming; Okabe, Yoji
Abstract: Lamb waves can be used in carbon fiber reinforced plastics (CFRP) for establishing both structural health monitoring systems and nondestructive inspection techniques. In this study, we investigated the dispersion relation of Lamb waves propagating in a cross-ply CFRP laminate. Using a formalism of the multi-layer Lamb wave model, we compared a homogeneous single-layer model and multi-layer models. The results suggest that the velocity of the S0 mode was the same for all the models in the low-frequency region. Thus, the use of homogeneous parameters is valid for the S0 mode. However, it was found that in high-frequency regions, there was a discrepancy between the velocities of Lamb wave modes for the homogeneous model and multi-layer models. This is because Lamb waves can be localized in a particular layer, and the velocity can be affected by the stiffness constants of the layer. This work elucidates the characteristics of Lamb wave propagation by showing that the stacking sequence of the laminate can have an effect on the wave velocities and wave structures, enabling researchers to improve Lamb wave-based defect detection.